Penerapan Model Pembelajaran Kooperatif Tipe Pair Checks di SMP Negeri 19 Tanjung Jabung Timur - Rozana, Rina (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2021)
This study aims to apply the cooperative learning model type Pair Checks in SMP Negeri 19 Tanjung Jabung Timur. This type of research is Classroom Action Research (PTK), conducted in two cycles. Each cycle includes planning, acting and observing, evaluating and reflecting. The subjects of this study were students of class VIII.C of SMP Negeri 19 Tanjung Jabung Timur. Data collection techniques in the study were in the form of observation sheets, student worksheets, written tests and documentation. The instruments used in this research were syllabus, lesson plan and observation sheet. The data analysis used is descriptive qualitative. The results showed that the implementation of the Pair Checks type of cooperative learning can improve learning outcomes and learning activities of students. This is evidenced by the increase in the average learning outcomes of students from cycle I to cycle II, where the average pre-cycle final test result was 71.80 in sufficient categories, while the average final result of cycle I was 77.14 good categories. , and in cycle II showed an increase with the average final learning outcomes is 82.17 with very good category. Thus it can be concluded that the implementation of the cooperative learning model type Pair Checks is very good where students look more active in class.Â